(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
Reducing productivity, outbreak of insects and diseases, and decreasing in physical and cup quality are major problems for Arabica coffee cultivation in medium altitude. The aim of this study was to investigate the effect of altitude on physical quality in eight genotypes of Arabica coffee. This research was conducted at two locations i.e. Andungsari Research Station-Bondowoso (1250 m asl. as high altitude) and Kalibendo Estate-Banyuwangi (700 m asl. as medium altitude). Randomized complete block design was used with three replications. Collected data consisted of outturn, weight of 100 beans, shape bean normality, apparent swelling, bulk density before and after roasting. Combined analysis on the physical quality traits of green bean showed genotype x altitude interactions on weight of 100 beans, percentage of normal beans and percentage of empty bean. Altitude significantly influenced coffee outturn. Decreasing in altitude from 1.250 m asl. to 700 m asl. caused declining in the outturn as much 32.9%. BP 700A, K 29, K 34, K 79, and K 99 were genotypes that stable to produce normal bean and empty beans at high and medium altidute, while K 8, K 130, and SIG were genotypes with high normal beans at high altitude but not stable. Genotype x altitude interaction did not occur for physical quality of other variables of outturn, bulk density before and after roasting, apparent swelling, percentage of round beans, percentage of elephant beans, and percentage of triage beans. Altitude showed significant effect on all of physical quality of bean variables.